2017
DOI: 10.1016/s0735-1097(17)33609-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Cardiac Myosin-Binding Protein C to Cardiac Troponins for the Early Diagnosis of Acute Myocardial Infarction

Abstract: ORIGINAL RESEARCH ARTICLE ORIGINAL RESEARCH ARTICLE BACKGROUND: Cardiac myosin-binding protein C (cMyC) is a cardiacrestricted protein that is more abundant than cardiac troponins (cTn) and is released more rapidly after acute myocardial infarction (AMI). We evaluated cMyC as an adjunct or alternative to cTn in the early diagnosis of AMI. METHODS:Unselected patients (N=1954) presenting to the emergency department with symptoms suggestive of AMI, concentrations of cMyC, and high-sensitivity (hs) and standard-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Notably, the cMyC has a higher efficacy for ruling out (safe) and ruling in patients than hs-cTn, while the diagnostic accuracy is similar [96]. Another study also demonstrates that cMyC has discriminatory power comparable to hs-cTn and may perform favorably early after symptom onset [97].…”
Section: Cardiac Myosin-binding Protein C (Cmyc)mentioning
confidence: 87%
“…Notably, the cMyC has a higher efficacy for ruling out (safe) and ruling in patients than hs-cTn, while the diagnostic accuracy is similar [96]. Another study also demonstrates that cMyC has discriminatory power comparable to hs-cTn and may perform favorably early after symptom onset [97].…”
Section: Cardiac Myosin-binding Protein C (Cmyc)mentioning
confidence: 87%
“…In contrast to myocardial serum markers, which are highly sensitive and specific, 40 there is a lack of cerebral injury markers. This is the case especially in cardiac surgery, where cardiotomy suction and cell salvage is used frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic profile of cMyC has been tested clinically and compared to cardiac troponins in a retrospective analysis of 7,000 sera from approximately 2,000 patients in the Advantageous Predictors of Acute Coronary Syndromes Evaluation (APACE) cohort presenting with suspected non ST-segment elevation myocardial infarction (NSTEMI) of whom 340 had an adjudicated AMI. Analysis, confined to the initial presentation blood sample, showed that cMyC is at least as good as cardiac troponin measured with the leading assays in predicting the diagnosis of AMI, mortality and future cardiovascular events [6]. Additionally, cMyC signalled improved triage over hs-cTnT of pre-hospital patients having blood drawn in the ambulance just 70 min after symptom onset [7].…”
Section: Introductionmentioning
confidence: 99%